Potret Solusi Alkitab bagi Generasi Z Penderita Sindrom Fear of Missing Out - Setyobekti, Andreas Budi; Wariki, Valentino; Anu, Kezya Jesika Maria (Sekolah Tinggi Teologi Kalvari Manado, 2024)
Abstract: There are two factors that influence FoMO in generation Z consisting of internal factors and external factors. Internal is found to have a low psychological need for relatedness and self. Meanwhile externals include transparency of social media information, age, social upmanship, and conditions of relative deprivation. Efforts to handle FoMO in generation Z based on a Biblical perspective are to use assistance or mentoring to generation Z who are FoMO. The method used in this research is qualitative. The approach taken is a literature study. Through this approach, researchers examine existing literature sources in order to obtain a logical thinking construct regarding FoMO. The Bible consistently shows how God cares for His people from generation to generation. This consistency of God's providence also applies to generation Z, especially those who experience FoMO. The essence of the Lord's Prayer is a form of God's openness in presenting His providence holistically to all believers from generation to generation. Abstrak: Ada dua faktor yang mempengaruhi FoMO pada generasi Z terdiri dari faktor internal dan faktor eksternal. Internal adalah ditemukan rendahnya kebutuhan psikologis akan relatedness dan self. Sementara ekstenal meliputi transparansi informasi media sosial, usia, social-upmanship, dan kondisi deprivasi relative. Upaya penanganan FoMO pada generasi Z berdasarkan perspektif Alkitab adalah menggunakan pendampingan atau mentoring kepada generasi Z yang FoMO. Metode yang digunakan dalam penelitian ini adalah kualitatif. Pendekatan yang dilakukan adalah studi pustaka. Melalui pendekatan ini peneliti mengkaji dari sumber literatur yang ada agar diperoleh konstruk berpikir yang logis berkenaan dengan FoMO. Alkitab secara konsisten memperlihatkan cara Allah memelihara umat-Nya dari generasi ke generasi. Konsistensi providensia Allah ini pun berlaku bagi generasi Z terkhusus mereka yang mengalami FoMO. Esensi Doa Bapa Kami merupakan salah satu bentuk keterbukaan Allah dalam menyajikan providensianya secara holistik bagi seluruh orang percaya dari generasi ke generasi.